Guía de verificación para el auditor, sobre el nivel de cumplimiento de la política de Gobierno Digital (Habilitador de Arquitectura) (2023)
The Colombian government developed the digital government policy to be adopted by public entities, but its adoption has generated in the entities situations of saturation and confusion of the standard and deficient and non-objective evaluations by the auditor. For this reason it is necessary to develop a verification guide for the auditor, which allows him to measure the level of compliance with the architecture enabler of the digital government policy and its management model, adopting a method of qualitative documentary research, analysis and observation techniques through which to explain and describe the principles, domains, guidelines, guidelines and deliverables that comprise it and the construction of a working paper for the auditor that allows him to measure effectively and efficiently the adoption of the policy.